2016
DOI: 10.1002/ejhf.486
|View full text |Cite
|
Sign up to set email alerts
|

Thirty‐year trends in heart failure hospitalization and mortality rates and the prognostic impact of co‐morbidity: a Danish nationwide cohort study

Abstract: AimsWe examined 30-year nationwide trends in heart failure hospitalization and mortality rates, and the prognostic impact of co-morbidity. Methods and resultsWe conducted a population-based cohort study of 317 161 patients with first-time inpatient hospitalizations for heart failure during 1983-2012. We computed the standardized hospitalization rate and 5-year mortality risk. Co-morbidity levels and calendar periods of diagnosis were compared by means of mortality rate ratios (MRRs) based on Cox regression. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
120
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 147 publications
(136 citation statements)
references
References 28 publications
12
120
3
1
Order By: Relevance
“…The improvement of in‐hospital mortality might have resulted from the American College of Cardiology/American Heart Association guidelines updated in 2005, which included more‐robust evidence from clinical trials. The data from a Danish nation‐wide cohort study also showed that mortality rates declined consistently from 1983 to 2012, and its reduction was independent of age, sex, and comorbidity burden 17. These changes might have affected the results of our current study.…”
Section: Discussionmentioning
confidence: 71%
“…The improvement of in‐hospital mortality might have resulted from the American College of Cardiology/American Heart Association guidelines updated in 2005, which included more‐robust evidence from clinical trials. The data from a Danish nation‐wide cohort study also showed that mortality rates declined consistently from 1983 to 2012, and its reduction was independent of age, sex, and comorbidity burden 17. These changes might have affected the results of our current study.…”
Section: Discussionmentioning
confidence: 71%
“…Advances in both the medical and device based treatments, have been associated with improved survival rates in patients with HF in many [17][18][19][20] but not all national registry-based studies. 21 Age-standardized death rates from heart failure have been reported to decrease by 40% in seven European countries between 1987 and 2008.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Still, cardiovascular diseases remain a leading cause of death worldwide, 5 underscoring the need for further research. Registries constitute an important source of data for cardiovascular research in Denmark.…”
Section: Introductionmentioning
confidence: 99%